(3GdJShjb hGdGSJgdGc GdZPGFj aj GdLRGFQ (B:s (3GdeaGgje ,GdJhLgGJ hHYV GdfUGFM (B/s - (3TjNj, ceGds ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
-(3bWGY GdehGO GdZPGFjI aj GdLRGFQ ,hGbY hBaGb GdadGMI eY JWhQ bWGY GdUfGYI GdZPGFjI hNOeGJ GdeWGYe hGdGcd GdSQjY ,dPdc JShjb GdehGO GdZPGFjI eagheg hfSjjQ YQV GdefJhL GdZPGFj eY GdJLGQI GdGdcJQhfjI ddehGO GdZPGFjI hHGdJGdj JWhQ GdefJhL GdZPGFj aj GdCShGb Gs
(3eQGLY U(B.265-280s
Keywords: (3GdCZPjI(B- (3JShjbs